Differences in Mood, Optimism, and Risk-Taking Behavior Between American and Chinese College Students - Wang, Jiao; Cui, Ruifeng; Stolarz-Fantino, Stephanie; Fantino, Edmund; Liu, Xiaoming (Frontiers in Psychology, 2022)
Mood and optimism have been demonstrated to influence risk taking decisions however the literature on mood, optimism, and decision making is mixed and conducted primarily with western samples. The present study sought to address this gap in the literature by examining the impact of mood and dispositional optimism on risk taking and whether these associations differed between undergraduate students from the United States (N=141) and the People’s Republic of China (N=90). Both samples completed a dispositional optimism questionnaire and an autobiographical mood induction task. They were then tasked with choosing to complete the Raven’s Advanced Progressive Matrices reasoning task on easy, medium, or hard difficulty for hypothetical money. Selecting harder difficulties was interpreted as more risk taking due to higher chance of failure. More positive mood and higher dispositional optimism were associated with decreased risk taking, i.e. selecting easier puzzle difficulties, in the American sample but increased risk taking decisions, i.e. selecting harder difficulties, in the Chinese sample (p<.05 for all). These findings suggest that the mixed literature on the effect of mood and optimism on decision making may be due to in part to national and/or cultural influences.